A elasticidade das fontes de energia renováveis e não renováveis no Pib brasileiro no período de 1970 a 2005 - Santos, Francisco Evandro de Sousa (2008)
This study aims to measure the elasticity of renewable energy and non-renewable in the Brazilian GDP. Using a Cobb-Douglas production function with the following variables: the real annual GDP, the real gross fixed capital formation, the number of taxpayers, renewable energy sources and non-renewable, both measured in tep. The main result of this work shows that a small technical rate of substitution of nonrenewable energy by renewable ones corroborate the vocation of Brazil in favor of a clean and renewable energetic matrix.